Sociology : A guide to problems and literature. - Bottomore, Tom (London George Allen & Unwin L T D, 1962)
First published in 1962, this seminal work is an introduction to sociology in a world context, and a sophisticated guide to the major themes, problems and controversies in contemporary sociology. The book remains unique in its organisation and presentation of sociological ideas and problems, in it s lack of insularity (its wide coverage of diverse types of society and of sociological thought from various cultural traditions), and in its systematic connection of sociology with the broad themes of modern social and political thought.
Keywords: Sociology